Pendidikan Holistik dalam Merangkul Spiritualitas dan Pengetahuan Empiris - Ika Ika; Khoirun Nisa; Ivan Ilham Riyandi; Fani Laffanillah (Concept: Journal of Social Humanities and Education, 2025)
Spiritual well-being in psychology is used to discuss the process of achieving spiritual conditions in individuals. Spiritual well-being is a concept regarding an innate state, has elements of motivation or drive to find the purpose of one's life, is dynamic and subjective in nature, and focuses on a certain uniqueness which is then believed to be the truth. One way to improve spiritual well-being is through dhikr activities, which are usually used as one of the psychotherapies in Islam. Epistemology as a branch of philosophy determines the character of knowledge, even determining the truths that are considered worthy of being accepted, and which ones should be rejected. Therefore, there are a number of questions that are usually asked to examine the issues in epistemology, namely what is knowledge, what are the sources and bases of knowledge? Is this knowledge a definite truth or just a guess? To answer all questions regarding the epistemology of knowledge, this article will examine in more depth the theories of knowledge and truth in epistemology. The method used in writing this article is a literature study. After presenting several explanations from various literature sources, it can be concluded that it is almost impossible to talk about "knowledge" without considering things about "truth".